Aqueous inorganic coating agent and coating method
Patent Information
- Application Number
- JP2025062053
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2025-04-03
- Publication Date
- 2026-10-16
- Estimated Expiration
- 2045-04-03
AI Technical Summary
【0007】 本開示によれば、基材との密着性に優れる被膜を形成できる水性無機コート剤、およびこの水性無機コート剤を用いたコーティング方法が提供される。
Smart Images

Figure 2026168712000001_ABST
Abstract
Description
[Technical Field]
[0001] The present invention relates to an aqueous inorganic coating agent and a coating method. [Background technology]
[0002] Conventionally, coating agents aimed at preventing contamination of substrates are known. For example, Patent Document 1 discloses an aqueous inorganic coating agent that is applied to the surface of an organic or inorganic substrate to form a superhydrophilic transparent inorganic film. [Prior art documents] [Patent Documents]
[0003] [Patent Document 1] Patent No. 4658093 [Overview of the Initiative] [Problems that the invention aims to solve]
[0004] Typically, the substrate surface is polished before applying the coating agent. However, it has been found that water-based coating agents do not adhere well to polished substrates.
[0005] The present disclosure aims to provide an aqueous inorganic coating agent capable of forming a film with excellent adhesion to a substrate, and a coating method using this aqueous inorganic coating agent. [Means for solving the problem]
[0006] This disclosure includes the following aspects: [1] Alkaline colloidal silica and At least one of a sodium phosphate compound and a potassium phosphate compound, Boric acid and, An aqueous inorganic coating agent containing an inorganic abrasive. [2] The aqueous inorganic coating agent according to the above [1], wherein the inorganic abrasive contains one or two or more selected from the group consisting of aluminum oxide, cerium oxide, and mesoporous silica. [3] The aqueous inorganic coating agent according to the above [1] or [2], further comprising an inorganic curing agent containing a metal element. [4] The aqueous inorganic coating agent according to the above [3], wherein the inorganic curing agent contains a metal stannate. [5] The aqueous inorganic coating agent according to the above [3] or [4], wherein the inorganic curing agent contains one or two or more selected from the group consisting of potassium stannate, sodium stannate, zinc stannate, zinc hydroxide, and indium tin oxide. [6] (i) after applying the aqueous inorganic coating agent according to any one of the above [1] to [5] to the surface of a base material, polishing the surface of the base material with an electric polisher or an electric sander, or (ii) polishing the surface of the base material and applying the aqueous inorganic coating agent by means of an electric polisher or electric sander equipped with a buff impregnated with the aqueous inorganic coating agent according to any one of the above [1] to [5], and removing the inorganic abrasive with water, the coating method. Effects of the Invention
[0007] According to the present disclosure, an aqueous inorganic coating agent capable of forming a coating film excellent in adhesion to a base material, and a coating method using the aqueous inorganic coating agent are provided. Brief Description of the Drawings
[0008] [Figure 1A] This is a photograph of a part of a solar panel (Application Example 1) applied with the aqueous inorganic coating agent of Example 2. [Figure 1B] This is a probe scanning microscope image (size: 1 μm × 1 μm) of a part of a solar panel (Application Example 1) applied with the aqueous inorganic coating agent of Example 2. [Figure 1C]This is a nanosearch microscope (size: 500 nm × 400 nm) image of a portion of the cross section of a solar panel (Application Example 1) treated with the aqueous inorganic coating agent of Example 2. [Figure 1D] This is the result of elemental analysis at an arbitrary point on the cross-sectional surface of a solar panel (Application Example 1) treated with the aqueous inorganic coating agent of Example 2, using an SEM-EDX analyzer (FE-SEM S-4800, manufactured by Hitachi High-Technologies Corporation). [Figure 1E] This is a photograph of the solar panel (Application Example 1) treated with the aqueous inorganic coating agent of Example 2, taken after it had been installed for a certain period of time and then splashed with water. [Figure 2A] This is a photograph of a portion of a solar panel (Comparative Application Example 1) treated with the aqueous inorganic coating agent of Comparative Example 1. [Figure 2B] This is a probe scanning microscope image (size: 1 μm × 1 μm) of a portion of a solar panel (Comparative Application Example 1) treated with the aqueous inorganic coating agent of Comparative Example 1. [Figure 3] This is a photograph of a portion of a bathroom tile (Application Example 2) treated with the aqueous inorganic coating agent of Example 4. [Figure 4] This is a photograph of a portion of a bathroom tile (Comparative Application Example 2) treated with the aqueous inorganic coating agent of Comparative Example 1. [Figure 5] This is a photograph taken on a snowy day 6 months after the automobile windshield (Application Example 3) treated with the aqueous inorganic coating agent of Example 1 was put to use. [Figure 6] This is a photograph of a portion of the mirror of a public hot spring facility (Application Example 4) treated with the aqueous inorganic coating agent of Example 1. [Figure 7] This is a photograph of a portion of the wall glass of an outdoor building (Application Example 5) treated with the aqueous inorganic coating agent of Example 1. [Figure 8A] This is a photograph of a portion of the stainless steel door of an elevator (Application Example 6) treated with the aqueous inorganic coating agent of Example 3. [Figure 8B] This is a photograph of a portion of the inside of the stainless steel car of an elevator (Application Example 6) treated with the aqueous inorganic coating agent of Example 3. [Figure 9]This is a photograph of a portion of a resin tape inside a railway vehicle (Example 7) that was coated with the aqueous inorganic coating agent of Example 4. [Figure 10A] This is a photograph showing the surface of the glass plate before water was sprayed on it in Experimental Example 1. [Figure 10B] This is a photograph showing the appearance of the glass plate surface when water is sprayed onto it in Experiment Example 1. [Figure 10C] This is a photograph showing the state of the glass plate surface after water was sprayed on it in Experiment Example 1. [Modes for carrying out the invention]
[0009] [Water-based inorganic coating agent] The aqueous inorganic coating agent of this disclosure comprises alkaline colloidal silica, at least one of a sodium phosphate compound and a potassium phosphate compound, boric acid, and an abrasive.
[0010] "Aqueous" means that the solvent is water. "Inorganic" means that it is not an organic substance. "Organic substance" means a compound containing carbon atoms (C). "Aqueous inorganic coating agent" means a coating agent in which the solvent is water and no organic substances are added. However, the presence of unavoidable organic substances in aqueous inorganic coating agents is acceptable. The presence of organic substances below the detection limit in aqueous inorganic coating agents is acceptable.
[0011] The following are possible reasons why conventional water-based coatings do not adhere well to polished substrates: Polishing removes dirt and activates the substrate surface, generating hydroxyl groups (OH groups) on the substrate surface. These OH groups react with oxygen atoms in the atmosphere to form an oxide film on the substrate surface. Since this oxide film is water-repellent, it is thought to inhibit adhesion between the water-based coating applied thereafter and the substrate.
[0012] The aqueous inorganic coating agent of this disclosure contains an abrasive along with alkaline colloidal silica. Therefore, when the aqueous inorganic coating agent of this disclosure is applied and polished, the surface of the substrate is activated while avoiding contact with the atmosphere, and the OH groups generated by the activation can quickly chemically bond with the colloidal silica. In addition, the abrasive removes dirt from the surface of the substrate. As a result, the adhesion between the coating agent and the substrate is improved.
[0013] As described above, polishing and coating are performed simultaneously, resulting in a uniform coating with few pinholes. This also improves the strength of the coating and allows for thinner films.
[0014] Furthermore, the film formed by the aqueous inorganic coating agent of this disclosure (hereinafter sometimes referred to as the "anti-fouling film") exhibits superhydrophilicity. As a result, dirt adhering to the substrate is easily washed away with water. The removal of dirt by water is referred to as the self-cleaning action. The self-cleaning action is exhibited, for example, by rainfall or washing with water. In this disclosure, anti-fouling properties refer to the performance resulting from the self-cleaning action in addition to the antistatic effect inherent in the aqueous inorganic coating agent.
[0015] "Superhydrophilicity" refers to a water contact angle of 15 degrees or less (especially 10 degrees or less). The water contact angle can be measured in accordance with JIS R 3257 Test method for wettability of substrate glass surfaces (static droplet method).
[0016] Superhydrophilicity is obtained by sodium phosphate compounds and potassium phosphate compounds (hereinafter sometimes collectively referred to as "alkali metal phosphates"). Alkali metal phosphates are hygroscopic or water-retaining. When moisture from the atmosphere is attracted to alkali metal phosphates, the hydrophilic groups (SiOH groups) of alkaline colloidal silica and hydroxide ions (OH) are attracted to them. -It combines with the aqueous inorganic coating agent and is retained as trace amounts of moisture on the film formed by the aqueous inorganic coating agent. As a result, the antifouling film exhibits superhydrophilicity. The moisture may be present in the atmosphere. Even such trace amounts of moisture will result in superhydrophilicity.
[0017] In other words, the aqueous inorganic coating agent of this disclosure provides a highly durable antifouling coating with superhydrophilicity and high adhesion.
[0018] Conventionally, photocatalysts used in antifouling coatings exhibit hydrophilicity in response to ultraviolet light. However, the coating agent of this disclosure can exhibit superhydrophilicity through contact with the atmosphere, even in the absence of ultraviolet light.
[0019] Organic fluorine compounds (PFAS, PFOA, etc.), such as fluororesins, are also used in antifouling coatings. However, concerns have recently arisen regarding the environmental impact of PFAS, PFOA, etc. The coating agent disclosed herein can exhibit excellent antifouling properties without using organic fluorine compounds.
[0020] Typically, the substrate surface is cleaned and rinsed, then polished and rinsed before the coating agent is applied. However, with the aqueous inorganic coating agent of this disclosure, polishing (dirt removal and activation) and antifouling coating of the substrate surface can be performed with a single material. Therefore, the application process is simplified, resulting in significant cost advantages.
[0021] The following describes in detail the aqueous inorganic coating agent and the coating method using the aqueous inorganic coating agent in the embodiments of this disclosure, but the present invention is not limited to these embodiments.
[0022] The solid content concentration of the aqueous inorganic coating agent is not particularly limited and is set appropriately according to the application and purpose. The solid content concentration of the aqueous inorganic coating agent may be 0.1 to 25% by mass, in which variation in film thickness can be suppressed. When used on inorganic substrates where smoothness and transparency are required, the solid content concentration of the aqueous inorganic coating agent may be 5.0 to 25.0% by mass, 10.0 to 25.0% by mass, or 15.0 to 22.0% by mass. When used on organic substrates, the solid content concentration of the aqueous inorganic coating agent may be 5.0 to 25.0% by mass, 10.0 to 22.0% by mass, or 15.0 to 20.0% by mass.
[0023] Solid content is also called non-volatile content. The solid content of aqueous inorganic coating agents is the residue after heating. The solid content concentration can be calculated from the residue after heating the aqueous inorganic coating agent at 200°C for 20 minutes, in accordance with JIS K 5601-1-2, the method for measuring residue after heating.
[0024] The content of each component is the ratio of the solid content concentration (heated residue) of that component to the total solid content concentration (heated residue) of the aqueous inorganic coating agent.
[0025] The pH of the aqueous inorganic coating agent is not particularly limited and may be in the neutral range. For example, the pH of the aqueous inorganic coating agent may be 5.0 to 9.0 or 6.0 to 8.0.
[0026] The specific gravity of the water-based inorganic coating agent, excluding the inorganic abrasive, is about the same as that of water. The specific gravity of the water-based inorganic coating agent, excluding the inorganic abrasive, is approximately 1.05 to 1.08. The viscosity of the water-based inorganic coating agent, excluding the inorganic abrasive, is also about the same as that of water. The viscosity of the water-based inorganic coating agent, excluding the inorganic abrasive, is approximately 1.0 mPa·s at 20°C.
[0027] (Alkaline colloidal silica) Alkaline colloidal silica crosslinks to form a coating on the substrate. Alkaline colloidal silica is negatively charged colloidal silica. In the aqueous inorganic coating agent of this disclosure, colloidal silica is usually negatively charged and exists as alkaline colloidal silica. Colloidal silica is also called silica sol.
[0028] Colloidal silica is a colloidal particle mainly composed of silicic acid (SiO2) or hydrated silicic acid. In aqueous inorganic coating agents, the surface of colloidal silica contains SiOH groups and OH groups. - Numerous such particles exist. As a result, an electrical double layer is formed, suppressing aggregation between colloidal silica particles, and the colloidal silica remains stably dispersed in the aqueous inorganic coating agent. The colloidal silica can be amorphous. The particle shape is not particularly limited and may be spherical or fragmented.
[0029] The average particle size of alkaline colloidal silica (hereinafter sometimes simply referred to as "colloidal silica") is not particularly limited and is appropriately selected according to the application and purpose. The average particle size of colloidal silica may be, for example, 3 to 100 nm, 5 to 70 nm, or 5 to 30 nm. Multiple types of colloidal silica with different average particle sizes may be used in combination.
[0030] The average particle size of colloidal silica is the particle size (D50) at which the cumulative volume, measured by a laser diffraction particle size analyzer, reaches 50%.
[0031] Colloidal silica may be obtained by dispersing one or more types of silica particles with different average particle sizes in water and stabilizing them with sodium dioxide.
[0032] Examples of commercially available colloidal silica include the "Snowtex (registered trademark)" series from Nissan Chemical Industries, Ltd., the "Quartron (registered trademark)" PL series manufactured by Fuso Chemical Co., Ltd., the "Cataloid (registered trademark)" series manufactured by JGC Catalysts and Chemicals Ltd., the "Adelite" series from ADEKA Corporation, the "Syton" series from Remet, "Nalcoag-1060" and "Nalcoag-ID21~64" from Nalco Chemical Company, and the "Ludox (registered trademark)" series from W.R. Grace & Co.
[0033] Content W of colloidal silica Si is appropriately set according to the application and purpose. The content W of colloidal silica Si may be, for example, 20 to 80 mass% or 30 to 70 mass% based on 100 mass% of the solid content of the aqueous inorganic coating agent.
[0034] (Sodium phosphate compound) As described above, the sodium phosphate compound contributes to the development of superhydrophilicity. Examples of the sodium phosphate compound include anhydrous sodium dihydrogen phosphate (NaH2PO4), sodium dihydrogen phosphate crystal (NaH2PO4·2H2O), disodium hydrogen phosphate crystal (Na2HPO4·12H2O), anhydrous trisodium phosphate (Na3PO4), trisodium phosphate crystal (Na3PO4·12H2O), tetrasodium pyrophosphate crystal (Na4P2O7), tetrasodium pyrophosphate crystal (Na4P2O7·10H2O), sodium dihydrogen pyrophosphate (Na2H2P2O7), sodium tripolyphosphate (Na5P3O 10 ), sodium tetrapolyphosphate (Na6P4O 13 ), sodium hexametaphosphate ((NaPO3) n ), acidic sodium hexametaphosphate ([Na x H y (PO3) x+y n ). These may be used singly or in combination of two or more kinds.
[0035] (Potassium phosphate compounds) As described above, potassium phosphate compounds contribute to the development of superhydrophilicity. Examples of potassium phosphate compounds include dipotassium dihydrogen phosphate (KH2PO4), dipotassium hydrogen phosphate (K2HPO4), and potassium metaphosphate. These can be used individually or in combination of two or more.
[0036] Total content of alkali metal phosphates W P The alkali metal phosphate content W is set as appropriate depending on the application and purpose. P The degree of hydrophilicity can be adjusted by this. Alkali metal phosphate content W P The amount of the solids component may be, for example, 0.5 to 60.0% by mass, 0.5 to 58.0% by mass, 0.5 to 20.0% by mass, or 0.5 to 10.0% by mass, based on 100% by mass of the solids content of the aqueous inorganic coating agent.
[0037] At least one of sodium dihydrogen phosphate and dipotassium hydrogen phosphate may be used because they are easily soluble in water.
[0038] (Boric acid) Boric acid (H3BO3) improves the adhesion between colloidal silica and the substrate. Boric acid also functions as a pH adjuster.
[0039] Boric acid content W B The amount is set appropriately depending on the application and purpose. Boric acid content W B The amount of the solids component may be, for example, 0.5 to 35.0% by mass, 0.6 to 30.0% by mass, 0.6 to 10.0% by mass, or 0.6 to 5.0% by mass, based on 100% by mass of the solids content of the aqueous inorganic coating agent.
[0040] Alkali metal phosphate content W P The boric acid content is W B and colloidal silica content W Si More is fine (W P >WB ,W Si In this case, the adhesion between the aqueous inorganic coating agent and the organic substrate can be further improved. This is because the alkali metal phosphate increases the viscosity of the aqueous inorganic coating agent, and the anchoring effect makes it easier for the aqueous inorganic coating agent to adhere to the organic substrate.
[0041] Colloidal silica content W Si The boric acid content is W B and alkali metal phosphate content W P More, W B and W P It can be of the same level (W Si >W B ≒W P In this case, the adhesion between the aqueous inorganic coating agent and the inorganic substrate can be further improved. This is because the inorganic substrate has OH groups on its surface and therefore reacts readily with colloidal silica.
[0042] (Inorganic abrasives) Inorganic abrasives contribute to improving the adhesion between the antifouling coating and the substrate. Inorganic abrasives do not contain carbon atoms. They exert their function when incorporated into coating agents that contain water as a solvent and do not contain organic substances. Because water has low viscosity, it prevents the inorganic abrasive particles from sticking together, and the abrasive function of the inorganic abrasive is not hindered.
[0043] The inorganic abrasive is not particularly limited and is appropriately selected depending on the substrate. Examples of inorganic abrasives include aluminum oxide, cerium oxide, mesoporous silica, kaolin, and bentonite. These can be used individually or in combination of two or more. Aluminum oxide is suitable for stainless steel, fiber-reinforced plastics (FRP), ceramics, and marble, for example. Cerium oxide is suitable for glass in general, for example. Mesoporous silica is suitable for glass, stainless steel, FRP, ceramics, and marble, for example.
[0044] Mesoporous silica may be blended with other inorganic abrasives. Mesoporous silica absorbs pressure from polishers and other equipment, suppressing damage to the substrate, and also adsorbs dirt that has been removed from the substrate, thereby enhancing the cleaning effect.
[0045] The amount of inorganic abrasive is set appropriately according to the application and purpose. The amount of inorganic abrasive may be, for example, 2 to 85% by mass, 5 to 80% by mass, or 10 to 80% by mass, based on 100% by mass of the solid content of the aqueous inorganic coating agent.
[0046] The average particle size or particle size of the inorganic abrasive is not particularly limited and is selected appropriately depending on the type of substrate. The table below shows an example of the correspondence between the substrate and the average particle size or particle size of the inorganic abrasive.
[0047] [Table 1]
[0048] The average particle size of the inorganic abrasive is the particle size (D50) at which the cumulative volume, measured by a laser diffraction particle size distribution analyzer, reaches 50%. The particle size of the inorganic abrasive is a value in accordance with JIS R 6001-1 2017 and JIS R 6001-2 2017.
[0049] (Inorganic curing agent) Aqueous inorganic coating agents may contain an inorganic curing agent. The inorganic curing agent contains a metal element. In an aqueous inorganic coating agent, the inorganic curing agent ionizes to generate metal ions. These metal ions adsorb onto the surface of colloidal silica, promoting aggregation of colloidal silica particles. This facilitates crosslinking (hardening) between colloidal silica particles, improving the strength of the coating.
[0050] The inorganic curing agent is not particularly limited as long as it contains a metal element. The metal element is not particularly limited. The inorganic curing agent is not particularly limited as long as it generates ionized metal in water. The inorganic curing agent may be water-soluble and colorless.
[0051] In terms of easily generating ionized metals, inorganic hardening agents may contain metal elements other than heavy metals, and may also contain alkali metals and alkaline earth metals. In terms of suppressing discoloration of the antifouling coating, inorganic hardening agents may be, for example, zinc hydroxide or indium tin oxide (ITO).
[0052] Examples of alkali metals include at least one selected from the group consisting of lithium (Li), sodium (Na), potassium (K), rubidium (Rb), cesium (Cs), and francium (Fr). Examples of alkaline earth metals include at least one selected from the group consisting of beryllium (Be), magnesium (Mg), calcium (Ca), strontium (Sr), barium (Ba), and radium (Ra).
[0053] The inorganic curing agent may contain a metal stinate salt. Examples of metal stinate salts include zinc stinate (Zn2SnO4), barium stinate (BaSnO3), sodium stinate (Na2SnO3), and potassium stinate (K2SnO3).
[0054] The inorganic curing agent may contain one or more selected from the group consisting of potassium stannate, sodium stannate, zinc stannate, zinc hydroxide, and indium tin oxide. These dissolve in water to form a colorless, transparent aqueous solution.
[0055] The amount of inorganic curing agent is set appropriately according to the application and purpose. The amount of inorganic curing agent may be 10 to 40% by mass, or 15 to 35% by mass, based on 100% by mass of the solid content of the aqueous inorganic coating agent, in order to suppress aggregation and precipitation.
[0056] (solvent) Water-based inorganic coating agents contain water as a solvent. Examples of water include purified water, deionized water, tap water, and deionized water. Because water does not easily evaporate during storage, it can suppress changes in the physical properties of the water-based inorganic coating agent over time. Furthermore, because water does not easily evaporate during application, the polishing function of the inorganic abrasive can be fully exerted.
[0057] (others) Aqueous inorganic coating agents may contain sodium silicate (also known as sodium silicate or water glass). Sodium silicate improves the adhesion between the antifouling coating and the inorganic substrate. Sodium silicate is a mixture of silicon dioxide (SiO2), sodium oxide (Na2O), and water (H2O). The molar ratio of SiO2 to Na2O is not particularly limited. The sodium silicate content is not particularly limited.
[0058] (Preparation method) Aqueous inorganic coating agents are prepared, for example, as follows: First, a predetermined amount of alkali metal silicate and boric acid are mixed. The boric acid used as a raw material may be in powder form or in aqueous solution. After adding water, the mixture is heated and stirred to dissolve the substances and obtain an aqueous additive solution. Separately, a predetermined amount of water and colloidal silica are thoroughly stirred at room temperature, or heated as needed. Furthermore, the above aqueous additive solution and, if necessary, an inorganic curing agent are added and stirred. Finally, a predetermined amount of inorganic abrasive is added and stirred to obtain an aqueous inorganic coating agent.
[0059] [Coating Method] The coating method of this disclosure comprises (i) applying the above-mentioned aqueous inorganic coating agent to the surface of a substrate, and then polishing the surface of the substrate with an electric polisher or electric sander, or (ii) applying the above-mentioned aqueous inorganic coating agent to the surface of a substrate and polishing the surface of the substrate with an electric polisher or electric sander, and then removing the inorganic abrasive with water.
[0060] (base material) The substrate to be treated with the aqueous inorganic coating agent is not particularly limited. The surface of the substrate may be formed of organic materials or inorganic materials. For convenience, a substrate having a surface formed of at least organic materials will be referred to as an organic substrate, and a substrate having a surface formed of at least inorganic materials will be referred to as an inorganic substrate.
[0061] Examples of inorganic materials include metals, stone, glass, mirrors, ceramics, and marble. Examples of metals include stainless steel, titanium, aluminum, and copper. The surface of metals may be formed by a plating layer. Examples of organic materials include various thermoplastic resins, thermosetting resins, FRP, and rigid films.
[0062] (1) Application and polishing of aqueous inorganic coating agent (i) After applying the above-mentioned aqueous inorganic coating agent to the surface of the substrate, the surface of the substrate is polished with an electric sander, or (ii) the surface of the substrate is polished and the aqueous inorganic coating agent is applied using an electric polisher equipped with a buff containing the above-mentioned aqueous inorganic coating agent. If the inorganic abrasive has settled, the aqueous inorganic coating agent should be stirred well before use to disperse the inorganic abrasive.
[0063] Method (i) In method (i), the aqueous inorganic coating agent is applied, for example, by spraying, by a portable semi-automatic coating machine, by a fixed indoor fully automatic or semi-automatic coating machine, or by an electric sander or electric polisher equipped with a buff. The amount of aqueous inorganic coating agent applied is not particularly limited.
[0064] Next, the surface of the substrate is polished using an electric polisher or electric sander. The electric polisher or electric sander used for coating and polishing may be the same or different.
[0065] Electric sanders are not particularly limited. Examples of electric sanders include orbital sanders and disc sanders. Commercially available electric sanders include the Makita Random Orbit Sander (model number: BO06050), the Cordless Random Orbital Sander (model number: BO1800), and the KYOCERA (formerly Ryobi) Square Orbital Sander (model number: NS-3250M).
[0066] Electric polishers are not particularly limited. Examples of electric polishers include double-action, single-action, and gear-action polishers. A commercially available electric polisher is the electric sander polisher (model number: PE-2100) manufactured by KYOCERA (formerly RYOBI).
[0067] The type of buff used is not particularly limited; for example, a short wool buff or a sponge buff can be used.
[0068] Method (ii) In method (ii), first, an aqueous inorganic coating agent is impregnated into, for example, a buffing pad. This buffing pad is then attached to an electric polisher or electric sander. By using this electric polisher or electric sander, the substrate surface is polished and the aqueous inorganic coating agent is applied simultaneously. The amount of aqueous inorganic coating agent impregnated into the buffing pad is not particularly limited.
[0069] (2) Removal of inorganic abrasives The inorganic abrasive does not participate in the curing process, and because the aqueous inorganic coating agent has low viscosity, it can be easily removed with water. If necessary, the substrate surface may be rubbed or squeegeeed while or after applying water. In this way, an antifouling film is formed on the substrate surface.
[0070] (Application) Water-based inorganic coatings can be used for a variety of applications. They can be applied to both outdoor and indoor facilities. The antifouling film formed by the water-based inorganic coating allows dirt to be easily removed by rain or washing.
[0071] Water-based inorganic coatings form a superhydrophilic, antifouling film and are used, for example, to prevent fogging of mirrors, glass, and painted surfaces, or to prevent static electricity, oil film, and fingerprint adhesion on car windows, mobile phones, TV and computer screens, and elevator button panels.
[0072] Water-based inorganic coatings form a highly adhesive, stain-resistant film that is difficult to peel off due to friction and exhibits superhydrophilicity over the long term. Therefore, water-based inorganic coatings are suitable for coating substrates that are subjected to friction during maintenance, such as exterior walls, windows, solar panels, sanitary ware, shop windows, glass display cases, windows in buildings and homes, and automobile windshields.
[0073] Water-based inorganic coating agents perform both surface polishing and antifouling coating with a single material. Therefore, the use of detergents containing surfactants is eliminated, contributing to a reduction in environmental impact. Furthermore, since water is not required except for the final removal of the inorganic abrasive, water-based inorganic coating agents are suitable for use in locations where large amounts of water are used or where transportation is difficult.
[0074] The aqueous inorganic coating agent is used, for example, to coat the cover glass of thousands of solar panels in a mega solar power plant. Using the aqueous inorganic coating agent of this disclosure, one solar panel (1.6 m²) 2 The amount of water used when coating the substrate is about 1.5L, which is necessary for removing the final inorganic abrasive. In contrast, the amount of water used in the conventional method, which uses different materials for removing dirt from the substrate surface, polishing, and applying an anti-fouling coating, is about 4L. When using the aqueous inorganic coating agent of this disclosure, one person can apply it to 45 to 60 solar panels per day. On the other hand, with the conventional method described above, one person can apply it to 18 to 22 solar panels per day. [Examples]
[0075] The present invention will be further described by the following examples, but the present invention is not limited thereto. In the examples, "%" means mass%.
[0076] Details of the materials used in the examples are as follows: • Colloidal silica (SiO2) Nissan Chemical Corporation, product name "Snowtex 40", average particle size 10-20 nm, solid content concentration 40.5% Alkali metal phosphates Anhydrous sodium dishydrogen phosphate, manufactured by Taihei Chemical Industry Co., Ltd., in powder form. Boric acid Taiyo Chemical Industry Co., Ltd., purified boric acid, powder form Sodium silicate Osaka Silicate Co., Ltd. Product name: "Special No. 1 Sodium Silicate", Molar ratio (SiO2 / Na2O) = 2.14 • Inorganic abrasives Cerium oxide, average particle size 2μm Alumina, particle size #3000 Mesoporous silica, average particle size 100 μm • Inorganic curing agent Potassium stinate aqueous solution, solid content concentration approximately 35% by mass
[0077] [Example 1] 10g of anhydrous sodium dihydrogen phosphate powder and 10g of purified boric acid powder were placed in a stainless steel heating container, and approximately 100g of water was added. The mixture was heated until it became colorless and transparent, dissolving each powder. More water was added until the total volume reached 100g to obtain an aqueous solution of the additives.
[0078] Separately, 100g of colloidal silica (Snowtex 40) was added to 3973g of water and stirred well at room temperature. The entire 100g of the above additive aqueous solution was then added and stirred well to obtain a mixture. 150g of inorganic curing agent (potassium stanate aqueous solution) was added to 850g of the obtained mixture and stirred well to obtain 1000g of curing agent-containing aqueous solution.
[0079] 900 g of an aqueous solution containing a hardening agent was mixed with 70 g of cerium oxide and 30 g of mesoporous silica as inorganic abrasives to obtain 1000 g of aqueous inorganic coating agent.
[0080] [Example 2] An aqueous inorganic coating agent was obtained in the same manner as in Example 1, except that an inorganic curing agent was not included.
[0081] [Examples 3-4] An aqueous inorganic coating agent was obtained in the same manner as in Example 1, except that the amounts of each component were as shown in Table 2.
[0082] The aqueous inorganic coating agents obtained in Examples 1-4 had a pH of 6.0-8.5 and a specific gravity of 1.07 excluding abrasives. Example 1 is suitable for general glass and mirrors. Example 2 is suitable for solar panels. Example 3 is suitable for organic substrates (FRP, film). Example 4 is suitable for stainless steel and ceramics and hardens at room temperature and with heating.
[0083] [Table 2]
[0084] [Comparative Example 1] An aqueous inorganic coating agent was prepared in the same manner as in Example 1, except that an inorganic abrasive was not added.
[0085] [Example of installation 1] Installation on solar panels (glass) A buffing pad (manufactured by Monotaro) attached to a single polisher (Kyocera (formerly Ryobi), electric sander polisher, model number: PE-2100) was soaked with 10g of the water-based inorganic coating agent from Example 2. Next, the surface (cover glass) of the solar panel was polished with the single polisher. After that, water was poured over the surface to remove the inorganic abrasive and obtain an anti-fouling coating.
[0086] Figure 1A is a photograph of a portion of a solar panel coated with the aqueous inorganic coating agent of Example 2. As can be seen from Figure 1A, the aqueous inorganic coating agent containing the inorganic abrasive of this disclosure provides an even coating of the solar panel surface.
[0087] Figure 1B is a probe scanning microscope image (size: 1 μm × 1 μm) of a portion of a solar panel coated with the aqueous inorganic coating agent of Example 2. As can be seen from Figure 1B, the aqueous inorganic coating agent containing the inorganic abrasive of this disclosure formed a dense film with unevenness (texture) on the substrate.
[0088] Figure 1C is a nanosearch microscope image (size: 500 nm × 400 nm) of a portion of the cross-section of a solar panel coated with the aqueous inorganic coating agent of Example 2. Figure 1D shows the results of elemental analysis of an arbitrary point on the surface of the cross-section using a SEM-EDX analyzer (FE-SEM S-4800, Hitachi HT Corporation). From Figures 1C and 1D, it is inferred that a monolayer SiOx film of approximately 50 nm is formed on the surface.
[0089] Figure 1E is a photograph of a solar panel treated with the aqueous inorganic coating agent of Example 2, after being installed for a certain period of time and then watered. Water was applied only to the right half of the photograph. As can be seen from Figure 1E, the dirt is washed away by the water, indicating that the antifouling properties are maintained over the long term.
[0090] [Comparative Construction Example 1] Construction on Solar Panels (Glass) A stain-resistant coating was formed on the solar panel in the same manner as in Example 1, except that 10g of the aqueous inorganic coating agent from Comparative Example 1 was impregnated into it.
[0091] Figure 2A is a photograph of a solar panel coated with the aqueous inorganic coating agent of Comparative Example 1. White unevenness in the coating can be seen.
[0092] Figure 2B is a probe scanning microscope image (size: 1 μm × 1 μm) of a portion of a solar panel coated with the aqueous inorganic coating agent of Comparative Example 1. It can be seen that a non-uniform coating was formed.
[0093] [Example of installation 2] Installation on bathroom tiles (ceramics) A buffing pad (manufactured by Monotaro) attached to a single polisher (Kyocera (formerly Ryobi), electric sander polisher, model number: PE-2100) was soaked with 10g of the aqueous inorganic coating agent from Example 4. Next, the surface of the tile was polished with the single polisher. After that, water was poured over the surface to remove the inorganic abrasive (alumina, etc.) and obtain an anti-fouling coating.
[0094] Figure 3 is a photograph of a portion of a bathroom tile that was coated with the aqueous inorganic coating agent of Example 4.
[0095] [Comparative Construction Example 2] Construction on bathroom tiles (ceramics) A stain-resistant coating was formed on the bathroom tiles in the same manner as in Example 1, except that 10g of the aqueous inorganic coating agent from Comparative Example 1 was impregnated into the tiles.
[0096] Figure 4 is a photograph of a portion of a bathroom tile coated with the aqueous inorganic coating agent of Comparative Example 1. As can be seen from Figures 3 and 4, the aqueous inorganic coating agent containing the inorganic abrasive of this disclosure allows for polishing and coating of fine details such as grout lines. As a result, a superhydrophilic film is uniformly formed over the entire substrate, exhibiting excellent stain resistance. We have separated the examples using the comparative coating agents.
[0097] [Comparative Construction Example 2] Construction on bathroom tiles (ceramics) A stain-resistant coating was formed on the bathroom tiles in the same manner as in Example 1, except that 10g of the aqueous inorganic coating agent from Comparative Example 1 was impregnated into the tiles.
[0098] Figure 4 is a photograph of a portion of a bathroom tile coated with the aqueous inorganic coating agent of Comparative Example 1. As can be seen from Figures 3 and 4, the aqueous inorganic coating agent containing the inorganic abrasive of this disclosure allows for polishing and coating of fine details such as grout lines. As a result, a superhydrophilic film is uniformly formed over the entire substrate, exhibiting excellent stain resistance.
[0099] [Example of application 3] Application to automobile windshield A buffing pad (manufactured by Monotaro) attached to a single polisher (manufactured by KYOCERA (formerly RYOBI), electric sander polisher, model number: PE-2100) was soaked with 10g of the water-based inorganic coating agent from Example 1. After spraying water onto the outer surface of the left half (in front of the driver's seat) of the car's windshield, the surface was polished for about one minute using the single polisher described above. Then, water was poured over the surface to remove the inorganic abrasive and obtain an anti-fouling coating.
[0100] [Comparative Installation Example 3] Installation on a car windshield First, a polishing solution was prepared by mixing water, cerium oxide, and mesoporous silica in the ratio of water:cerium oxide:mesoporous silica = 90% by mass:7% by mass:3% by mass. Next, water was applied to the outer surface of the right half (front of the passenger side) of the same automobile windshield used in Example 3. Then, the outer surface of the right half was polished with a single polisher for about 1 minute, in the same manner as in Example 3, except that the polishing liquid was used. After applying water to the surface to remove the inorganic abrasive, it was left to stand for 10 minutes. Finally, the aqueous inorganic coating agent of Comparative Example 1 was spray-applied to form a film.
[0101] Figure 5 is a photograph of a windshield on a snowy day, six months after the above coating was formed. It can be seen that the left half (in front of the driver's seat) has high transparency. This is thought to be because the coating was formed on the glass surface activated by the inorganic abrasive without contact with oxygen in the atmosphere, resulting in a uniform antifouling coating without pinholes. Such a uniform antifouling coating without pinholes exhibits superhydrophilicity.
[0102] On the other hand, streaks or fine water droplets remained on the glass of the right half (in front of the passenger seat). This is thought to be because the glass surface was activated by polishing and then came into contact with the atmosphere. When oxygen atoms in the atmosphere react with the activated glass surface, a water-repellent oxide film is formed on the glass surface. This oxide film reduces the adhesion between the glass surface and the aqueous inorganic coating agent applied later, causing pinholes to form. Therefore, the film does not exhibit superhydrophilicity, and it is thought that water droplets remained as shown in Figure 5.
[0103] [Example of installation 4] Installation on mirrors in a public bathhouse Except for impregnating the mirror with 10g of the aqueous inorganic coating agent from Example 1, an anti-fouling coating was formed on the mirror of the public bath in the same manner as in Application Example 1.
[0104] Figure 6 is a photograph of a section of a mirror in a public bathhouse that was coated with the aqueous inorganic coating agent of Example 1. The left side of the mirror is before coating (current state), and the right side is after coating. The mirror after coating is free of dirt, and water droplets do not adhere to it even due to the steam in the bathroom, demonstrating its superhydrophilic properties.
[0105] [Example of installation 5] Installation on glass walls of an outdoor structure (arena) Except for impregnating it with 10g of the aqueous inorganic coating agent from Example 1, an anti-fouling coating was formed on the arena's glass wall in the same manner as in Construction Example 1.
[0106] Figure 7 is a photograph of a portion of the glass wall of an outdoor structure (arena) that was coated with the aqueous inorganic coating agent of Example 1. After application, it was confirmed that fingerprint stains were removed from the glass wall and transparency was improved.
[0107] [Example of installation 6] Installation of stainless steel doors and stainless steel cages in elevators Except for impregnating 10g of the aqueous inorganic coating agent from Example 3, an antifouling coating was formed inside the stainless steel elevator door and cage in the same manner as in Example 1.
[0108] Figure 8A is a photograph of a portion of a stainless steel elevator door treated with the aqueous inorganic coating agent of Example 3. Figure 8B is a photograph of a portion of the stainless steel elevator car treated with the aqueous inorganic coating agent of Example 3. It was confirmed that the dirt was completely removed from the door and the inside of the car after treatment. Furthermore, when a mark was made on the treated surface with an oil-based pen, the mark was removed by applying water and lightly rubbing it.
[0109] [Example of application 7] Application to resin tape inside railway vehicles Except for impregnating it with 10g of the aqueous inorganic coating agent from Example 4, an antifouling coating was formed on the resin tape inside the railway vehicle in the same manner as in Example 1.
[0110] Figure 9 is a photograph of a portion of a resin tape inside a railway vehicle that was treated with the aqueous inorganic coating agent of Example 3. It was confirmed that the tape was completely free of dirt after treatment.
[0111] [Experimental Example 1] Coating of glass plate A stain-resistant coating was formed on the right half of a glass plate in the same manner as in Example 3, except that the aqueous inorganic coating agent of Example 2 was used. A coating was then formed on the left half of the same glass plate in the same manner as in Comparative Example 3.
[0112] After confirming that the entire surface of the glass plate was dry, a pattern was drawn on it with an oil-based pen (see Figure 10A), and it was exposed to the outdoors. After one week, it was confirmed that dirt had accumulated on the surface of the glass plate. When water was sprayed onto the glass plate, the oil-based ink on the right half lifted and ran off. On the other hand, no change was observed in the oil-based ink on the left half. Figure 10B is a photograph showing the state of the glass plate surface when water was sprayed on it in Experiment Example 1.
[0113] Furthermore, when water was sprayed over the entire surface of the glass plate, almost all of the oil-based ink on the right half lifted off. On the other hand, no change was observed on the left half. Figure 10C is a photograph showing the state of the glass plate surface when water was sprayed over it in Experiment Example 1. [Industrial applicability]
[0114] The aqueous inorganic coating agent of this disclosure can impart highly durable stain resistance to various substrates.
Claims
1. Alkaline colloidal silica and At least one of a sodium phosphate compound and a potassium phosphate compound, Boric acid and, An aqueous inorganic coating agent containing an inorganic abrasive.
2. The aqueous inorganic coating agent according to claim 1, wherein the inorganic abrasive comprises one or more selected from the group consisting of aluminum oxide, cerium oxide, and mesoporous silica.
3. Furthermore, the aqueous inorganic coating agent according to claim 1 or 2 further comprises an inorganic curing agent containing a metal element.
4. The aqueous inorganic coating agent according to claim 3, wherein the inorganic curing agent comprises a metal stainate salt.
5. The aqueous inorganic coating agent according to claim 3, wherein the inorganic curing agent comprises one or more selected from the group consisting of potassium stannate, sodium stannate, zinc stannate, zinc hydroxide, and indium tin oxide.
6. (i) After applying the aqueous inorganic coating agent described in claim 1 to the surface of the substrate, polish the surface of the substrate with an electric polisher or electric sander, or (ii) Polish the surface of the substrate with an electric polisher or electric sander equipped with a buff containing the aqueous inorganic coating agent described in claim 1 and apply the aqueous inorganic coating agent, and A coating method comprising removing the inorganic abrasive with water.
Citation Information
Patent Citations
Aqueous inorganic coating agent and aqueous solution thereof
JP4658093B2